Retaining Wall Innovation of Stone and Reinforced Concrete to Stand Guard Against Landslides and Earthquakes - Cahyono, Heru Setiyo; Arifin, Achmad Saiful; Ingsih, Ita Suhermin; Saefudin, Ruli; Mustofa, Imam (Journal Innovation of Civil Engineering (JICE), 2025)
In the landslide–prone terrains of Puri District, East Java, engineers have crafted a groundbreaking solution to a life–threatening problem: a hybrid retaining wall that fuses traditional batu kali masonry with reinforced concrete, designed to outlast both relentless soil creep and violent earthquakes. Standing 4.25 meters tall and stretching 20 meters across a fragile slope, this structure—embedded 1.5 meters into the earth—defies seismic forces amplified by climate change, withstanding horizontal accelerations of 0.19g and shear forces that spike 388% during quakes. Rigorous analysis reveals its secret: D16 steel bars, spaced as tight as 100 mm at stress hotspots, work in concert with locally quarried stone to balance cost and resilience. The wall’s success lies in numbers—sliding safety factors of 4.02 (normal) and 1.78 (seismic), bearing pressures grazing 99.9% of limits without failure—but its true victory is human. Shielding a riverside community from catastrophic landslides, it ensures roads stay open, homes remain intact, and daily life flows uninterrupted. As Indonesia battles rising rainfall and tectonic unrest, this innovation offers a replicable blueprint: marrying ancestral building wisdom with 21st–century engineering to turn vulnerability into durability. Keywords: Retaining Wall; Seismic Condition; Landslide Mitigation; Masonry Structure; Sustainable Infrastructure.